Lysine (protein) requirements of lactating sows. Issue 2 (25th May 2020) - Greiner, Laura; Srichana, Pariat; Usry, James L; Neill, Casey; Allee, Gary L; Connor, Joseph; Touchette, Kevin J; Knight, Christopher D
Abstract: Five experiments were conducted to evaluate the lysine (Lys) requirements of lactating sows. All diets were formulated to be isocaloric 3.46 Mcal ME/kg and met or exceeded National Research Council recommendations. In all studies, sow feed intake, body weight loss/gain, subsequent reproduction, and litter growth rate (LGR) were evaluated. The data were analyzed as randomized complete block design using generalized linear model in SAS with parity as a block. Two hundred and sixty-four primiparous sows (PIC Camborough 22) were randomly allotted to one of five lactation treatments (total Lys of 0.95%, 1.05%, 1.15%, 1.25%, and 1.35%) in Exp. 1 from August 2005 through October 2005. As daily total dietary Lys intake increased from 52.10 to 77.53 g, piglet ADG and daily litter gain linearly improved ( P < 0.01). From February 2007 through April 2007, 336 multiparous sows (parity 4 and older, PIC Camborough 29) were randomly allotted to one of five lactation treatments (total Lys 0.85%, 0.95%, 1.05%, 1.15%, or 1.25%) in Exp. 2. As dietary total Lys increased from 0.85% to 1.25% of the diet, there were no significant differences in litter performance, such as ADG, daily litter gain, and the number of pigs weaned. Experiment 3 was conducted from October 2008 through January 2009. Two hundred and seventy-nine primiparous gilts (PIC Camborough 29) were randomly allotted to one of five lactation treatments (total Lys 1.14%, 1.25%, 1.35%, 1.46%, and 1.57%). Actual total Lys intakes increased from 56.74 to 77.12 g/d. Feeding total dietary Lys quadratically decreased ( P < 0.01) weaning-to-estrus interval and increased percentage bred by 10 d ( P = 0.02). In Exp. 4, 200 sows (parity 4 and older, PIC Camborough 29) were randomly allotted to one of five treatments (0.85%, 0.95%, 1.05%, 1.15%, or 1.25% total Lys) from January 2008 through March 2008. As dietary total Lys increased from 42.40 to 66.15 g/d, sow body weight and LGRs were not influenced by dietary total Lys intakes. In Exp. 5, 324 parity 3 sows (PIC Camborough 29) were randomly allotted to one of five treatments (0.77%, 0.92%, 1.08%, 1.23%, and 1.38% total Lys) from August 2009 through October 2009. As daily dietary total Lys intake increased from 39.44 to 67.32 g, the percentage of sows bred by 10 d increased ( P = 0.02), as well as the LGR. A broken-line quadratic regression analysis demonstrated that the total Lys requirement for LGR for parity 1 females is calculated as 72.68 − [6.04 × (3.55 − LGR)] and for parity 3+ females as 92.03 − [11.9 × (4.24 − LGR)].